A savings subsidization system in a model of endogenous fertility and endogenous growth: an extension of Wigger (1999) - Ho, Chong Mun; Brian Dollery (John Wiley & Sons Australia, Ltd, 2006)
Population ageing is now an established demographic characteristic of many economies. Economists working in the endogenous growth theory tradition have sought to model the relationship between public pensions, financed on a 'Pay-As-You-Go' basis, and the growth in per capita incomes. The resultant intergenerational wealth redistribution from young to older people seems to decrease private savings, diminish capital accumulation, and lower the growth of per capita incomes. The underlying transmission mechanism appears to be a crowding out effect in private capital markets contingent upon the introduction of public pension systems. A growing literature exists on the interrelationships between public pension schemes, fertility rates and endogenous growth. Following Wigger's (1999) pioneering overlapping generations endogenous growth model, we extend this model to examine the effects of a savings subsidisation system on the rate of per capita income growth, fertility and voluntary intrafamily wealth transfers, where parents view children both as an insurance good and a consumption good. Moreover, children care about the consumption levels of their parents. An increase in contributions to a savings subsidised public pension scheme will crowd out private intergenerational transfers from the young to the old and thereby negate the usefulness of children as an insurance good.